Dapagliflozin cost-effectiveness analysis in heart failure patients in Egypt. (31st December 2022) - Abdelhamid, Magdy; Elsisi, Gihan Hamdy; Seyam, Ahmed; Shafie, Ahmed; Kirollos, Mary; Emad, Sandy; Mansy, Shady; Sobhy, Mohamed
Abstract: Aims: In Egypt, cardiovascular (CV) diseases are not only the cause of 33% of disability-adjusted life years but are also a leading cause of death. This study aimed to evaluate dapagliflozin's cost-effectiveness as an add-on to the standard of care (SOC) for the treatment of heart failure with reduced ejection fraction (HF-rEF) from the Egyptian healthcare system perspective. Materials and methods: A state transition model was utilized to assess the cost-effectiveness of dapagliflozin as an add-on to the SOC and a cost-minimization analysis was performed to compare dapagliflozin to sacubitril/valsartan, as they have had similar efficacy. Patients were stratified into four health states using the KCCQ-TSS, in addition to a CV and non-CV mortality health states. Urgent heart failure (HF) visits and hospitalizations were captured as transient states. Clinical parameters and baseline characteristics were based on the DAPA-HF trial, utility scores were extracted from published articles, and costs were derived from the Universal Health Insurance Authority national database. Deterministic and probabilistic sensitivity analyses were performed. Results: The treatment costs of HF-rEF patients receiving dapagliflozin compared to SOC are 47, 901EGP (10, 550) and 34, 377EGP (7, 572), respectively. The quality-adjusted life-years (QALYs) of dapagliflozin compared to SOC are 4.57 and 4.20, respectively. This resulted in an incremental cost per effectiveness ratio (ICER) of 36, 449EGP (8, 028) per QALY gained over the lifetime horizon, suggesting this is cost-effective. Results of the cost-minimization analysis showed cost savings where the annual costs of dapagliflozin vs. sacubitril/valsartan are 10, 914EGP (2, 404) and 32, 242EGP (7, 101), respectively. Conclusion: Dapagliflozin was found to be a highly cost-effective and cost-saving medication when compared to SOC and sacubitril/valsartan, respectively, in the treatment of HF-rEF from Egyptian healthcare system perspective. The ICER was below the willingness-to-pay threshold because dapagliflozin improved outcomes (less frequent hospitalization and mortality).